Assessment of GIC risk due to geomagnetic sudden commencements and identification of the current systems responsible. Issue 1 (29th January 2014) - Fiori, R. A. D.; Boteler, D. H.; Gillies, D. M.
Abstract During periods of enhanced geomagnetic activity, geomagnetically induced currents (GIC) flow in power systems potentially causing damage to system components or failure of the system. The largest GIC are produced when there are large rates of change of the geomagnetic field (dB/dt). It is well established that the main phase of a geomagnetic storm, particularly the magnetic substorms occurring during that period, is a cause of large GIC and hence a risk factor for power systems. However, some power system disturbances have been associated with the occurrence of a storm sudden commencement (SSC) prior to the main phase. We investigate the magnetic signature observed on the ground and the associated solar wind and interplanetary magnetic field (IMF) conditions for both SSC and sudden impulse (SI) events, which are grouped together as sudden commencements (SC). SCs are primarily attributed to a sudden enhancement of the magnetopause current. For some events, we show that there is a high‐latitude enhancement (HLE) of the SC amplitude and corresponding dB/dt. The limited spatial extent suggests an ionospheric current source. Examination of the polarity of the change in the X‐component magnetic field shows that the HLE is due to a sudden increase of the ionospheric convection electrojets. The occurrence of the HLE is more prevalent for SSC‐type SCs, SCs caused by coronal mass ejections as opposed to corotating interaction regions, and SCs associated with a large solar wind speed (vsw) prior to the SC or a large Δvsw at the time of the SC.